Effects of patient characteristics and comorbidities on temporal trends of low-flow, low-gradient aortic stenosis phenotypes. (25th November 2020) - Sen, J; Manning, T; Innes-Jones, K; Neil, C; Marwick, T.H
Abstract: Background: Aortic stenosis (AS) is a common primary heart valve disease in the elderly. Low-flow, low-gradient (LFLG) AS is an increasingly important phenotype. Purpose: To evaluate the temporal changes in incidence of severe AS phenotypes: paradoxical LFLG, classical LFLG and non-LFLG and explore risk factors that contribute to temporal trends. Methods: We analyzed 25, 507 consecutive transthoracic echocardiograms over 6½ years between 2013 and 2019 divided into deciles. LFLG-AS was defined as mean transvalvular pressure gradient <40 mmHg and stroke volume index (SVi) <35 mL/m 2, aortic valve area (AVA) <1 cm 2 or indexed AVA <0.6 cm 2 /m 2, with either normal (paradoxical LFLG) or decreased (<40%; classical LFLG) left ventricular ejection fraction. Trends and associations with patients characteristics and comorbidities were assessed over time in deciles. Results: Of 891 cases that fulfilled severe AS criteria, there were 536 cases of LFLG-AS (85 classical and 451 paradoxical LFLG-AS). There was a statistically significant increase in incidence of paradoxical LFLG-AS between each time interval (p<0.0001), while significant reduction in incidence of non-LFLG-AS (p=0.009) that was not seen with classical LFLG-AS (p=0.7) (Figure). More comprehensive echocardiographic assessment of relevant parameters over time assisted with identification of LFLG-AS cases. Intrinsic patient factors such as age and E/e' contributed towards the increasing trend of paradoxical LFLG-AS. There was a rising population aged over 70 years (p=0.01). Multivariate logistic regression analysis showed that age, sex, E/e', obesity, atrial fibrillation and heart rate were potential risk factors responsible for temporal trend towards rising paradoxical LFLG-AS incidence. There was also a gradual increase in number of patients with low transvalvular flow rate (<200mL/s) over time (p=0.04). Conclusion: The incidence of paradoxical LFLG-AS is rising in a hospital echocardiogram service. The parallel increase in LV filling pressure and age in AS patients suggests the increment in LFLG-AS is related to changes to the LV myocardium. Funding Acknowledgement: Type of funding source: None